Seismic responses of a subway station and tunnel in a slightly inclined liquefiable ground through shaking table test. Issue 116 (January 2019) - Haiyang, Zhuang; Xu, Wang; Yu, Miao; Erlei, Yao; Su, Chen; Bin, Ruan; Guoxing, Chen
Abstract: A lateral displacement of a soil layer caused by sand liquefaction in a slightly inclined ground may pose a serious threat to the seismic safety of subway stations and other large-scale underground structures. Owing to the sharp stiffness variation of the subway station–tunnel connection (STC), the seismic response of a subway station and tunnel near the connection differs from that of the normal part. Thus, this study presents an extensive shaking table test that focuses on the seismic response of the connecting part between a subway station and a running tunnel located under a slightly inclined (dip angle = 6°) liquefiable ground. Results demonstrate apparent asymmetric liquefaction distribution characteristics in the surrounding soil on both sides of the subway station. The asymmetric settlement of the ground surface and horizontal displacement of the slope was also analyzed. The non-uniform elevating of the subway station was also observed in the test. The STC could also aggravate the strain responses of a nearby tunnel structure in the longitudinal direction and those of a nearby column of a subway station. In comparison with the results obtained in the horizontally stratified ground, the distribution law of the strain responses of the subway station was also changed by the lateral liquefaction deformation of the slightly inclined ground. Highlights: Model test was conducted on a subway station and a tunnel in a liquefiable sloping site. The earthquake responses of station in this study are different from those in a level ground. Non-uniform liquefaction distribution on sides of station was found and analyzed. Non-uniform uplift of subway station in a liquefied sloping site was found and analyzed. Headwall aggravated the longitudinal strain response of tunnel and station's column.